Innovative East Asia : the future of growth - Yusuf, Shahid; Altaf, M. Anjum; Eichengreen, Barry (Washington, D.C. : World Bank, 2003)
The book provides an in-depth analysis of the policy trade-offs identified in the recently published 'can the East Asia Compete'? Its major contribution is that it shows how stability can be a stepping-stone to growth that is led by innovation, identifies and analyses the ingredients of an innovative economy, and discusses how these ingredients mesh with government policy and market initiatives
"A copublication of the World Bank and Oxford University Press."
Includes index.
Includes bibliographical references (p. 373-421).
osc 26/08/2016
Loans
Keywords: Investments, Foreign; Finance; Industrial policy; Technological innovations; Globalization; Social change; East Asia